Pengaruh Edukasi Terhadap Peningkatan Pengetahuan Dan Sikap Remaja Tentang Faktor Risiko Hipertensi Pada Gamers Di SMA Kota Semarang - Chairunnisa Putri, Nabilla; Musthofa, Syamsulhuda Budi; Sriatmi, Ayun (Madu : Jurnal Kesehatan, 2025)
Online games, which are popular among teenagers, may lead to a lifestyle that increases the risk of hypertension. Lack of knowledge and appropriate attitudes regarding the negative effects of online games is a major concern. This study aims to evaluate the effect of education on increasing adolescents' knowledge and attitudes about risk factors for hypertension due to the effects of online games in high schools in Semarang City. The research design used was a quasi-experimental with two groups (intervention and control), each of which was given a pre-test and post-test. The sample consisted of 227 students from SMA Teuku Umar and MA Husnul Khatimah who were selected using non-probability sampling. Data were collected through questionnaires and analyzed using paired t-test, Wilcoxon and Mann-Whitney tests. The results showed a significant increase in knowledge in the intervention group from an average of 10.80 to 15.00, while attitudes increased from an average of 60.79 to 64.21, but were not significantly different from the control group. This study concluded that there was a significant difference between the knowledge scores of the intervention group and the control group after education. However, there was no significant difference in attitude scores between the two groups after the intervention.